Challenges and Obstacles to Human Resource Management of the Indonesian National Police in the Utilization of UAV Technology - Marpaung, Irfan Satya Prasad; Halkis, Mhd; Susilo, Tarsisius (Universitas Negeri Semarang, 2024)
The utilization of Unmanned Aerial Vehicle (UAV) technology by the Indonesian National Police (Polri) offers significant potential in enhancing surveillance capabilities, supporting disaster response, border control, traffic monitoring, and various security operations. UAVs enable real-time data collection and remote monitoring, thereby increasing operational efficiency and reducing the risk to human personnel in dangerous environments. Nevertheless, despite these benefits, the implementation of UAVs within Polri is not without its challenges. These challenges are multifaceted, encompassing both technical aspects such as limited system integration, insufficient bandwidth, and battery life issues and non-technical factors, including institutional readiness, inter-agency coordination, and public perception. This study seeks to explore and map the key obstacles that hinder the effective deployment and utilization of UAV technology within Polri's operational framework. Among the most prominent challenges identified are the limited competencies of personnel in operating UAVs, the absence of standardized and comprehensive training programs, and the lack of a dedicated organizational unit specializing in UAV management. In addition, regulatory frameworks governing UAV use in national law enforcement are still evolving and often ambiguous, resulting in legal uncertainties and operational inefficiencies. Furthermore, supporting infrastructure such as maintenance facilities, software systems, and data security protocols remains inadequate in many regional units. The findings emphasize that the most pressing issues include not only the absence of technical know-how and system integration limitations but also the weak institutional regulation and strategic vision for UAV deployment. These results underline the urgent need for comprehensive capacity building, clearer inter-institutional guidelines, and sustainable investment in UAV-related infrastructure to ensure that the adoption of drone technology can effectively support Polri’s broader mandate of maintaining national security and public order.